(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The provision of textbooks in apartheid South Africa (1948-1994), a source of controversy and media interest in recent years, is placed in historical perspective, with particular reference to History textbook production. Michael W Apple (1993) proposes an analytical framework of political economy to enable better understanding of the tensions behind textbook production and distribution. During apartheid bureaucratic structures and commercial imperatives gave rise to a conformist ethos that stifled innovation. The textbook approval and adoption processes led publishers into adopting strategies to ensure approval for and approval of their textbooks. To avoid friction with education departments, editors urged self-restraint on their writers and instructed them in how to write officially approvable manuscripts. While some authors were disappointed, most wrote to satisfy their publishers, often resorting to copying the content and style of previously-approved textbooks. Focusing on History textbooks as a field of publishing history, this study synthesises existing primary and secondary sources, further supplemented by interviews with former History textbook writers and editors.